Nasopharyngeal Coil Dislocation of an Embolized Internal Carotid Artery Pseudoaneurysm - Ay, Nazli; Todt, Ingo; Sudhoff, Holger (Case Reports in Otolaryngology, 2021)
Objective. Severe epistaxis caused by ruptured intracranial pseudoaneurysms can be effectively treated by coil embolization. This is generally an efficient and safe procedure and provides sufficient protection recurrent epistaxis. However, complications such as aneurysm rupture, arterial dissection, bleeding, and emboli can occur. A dislocation of a nasopharyngeal coil is an extremely rare event. Patient. We present a case of a 61-year-old patient with a recurrent undifferentiated nasopharyngeal carcinoma (NPC) treated with severe epistaxis. Initially, epistaxis was successfully controlled by a nasal packing. Recurrent bleeding despite packing required a neuroradiological intervention. An intracranially ruptured pseudoaneurysm was detected by magnetic resonance imaging (MRI) and computed tomography (CT), originating from the internal carotid artery at the junction of the petrous part to the cavernous part. Coiling and endovascular plug embolization was performed for the treatment of aneurysm. Ten months later, the patient removed a foreign body out of his left nose. It was dislocated coil material due to radionecrosis. MRI confirmed sufficient embolization of the internal carotid artery. Conclusions. This case report highlights the possibility of a nasopharyngeal coil dislocation of an embolized internal carotid artery aneurysm emerging as a nasal foreign body.